2019
DOI: 10.1002/bjs.11391
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the introduction and evaluation of magnetic augmentation of the lower oesophageal sphincter for gastro-oesophageal reflux disease

Abstract: Background: Magnetic sphincter augmentation (MSA) is reported to be an innovative alternative to antireflux surgery for patients with gastro-oesophageal reflux disease. Although used in practice, little is known about how it has been evaluated. This study aimed to systematically summarize and appraise the reporting of MSA and its introduction into clinical practice, in the context of guidelines (such as IDEAL) for evaluating innovative surgical devices.Methods: Systematic searches were used to identify all pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…Overall, this systematic review demonstrates that the conclusions of included studies were not based on the evidence within the papers, which had methodological weaknesses. Our results are consistent with existing evidence that surgical innovations have been poorly reported [ 72 ]. Future work is needed to change how devices are used and evaluated after approvals, to allow transparent incremental evidence to be created to inform clinical practice and decision-making.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, this systematic review demonstrates that the conclusions of included studies were not based on the evidence within the papers, which had methodological weaknesses. Our results are consistent with existing evidence that surgical innovations have been poorly reported [ 72 ]. Future work is needed to change how devices are used and evaluated after approvals, to allow transparent incremental evidence to be created to inform clinical practice and decision-making.…”
Section: Discussionsupporting
confidence: 93%
“…In the USA, invasive devices are now subject to a pivotal clinical study as part of the FDA’s premarket approval pathway. The UK Medicines and Healthcare products Regulatory Agency (MHRA) does not specify the type of study required to achieve device approval, but the majority do not include a control group [ 72 ]. Pressure for reform is mounting.…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic reviews have demonstrated that outcome reporting in studies of innovative surgical procedures and devices focuses on short-term, clinical and technical outcomes 21 22. These outcomes are critical to assess in any early-phase study and are required for US FDA and the UK Medicines and Healthcare products Regulatory Agency approval 23 24.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review by Kirkham et al 30 evaluating the evidence of the device shows a concerning lack of unbiased evidence in the literature with no longterm safety demonstrated. Only one RCT has been carried out and this compared the surgery to medical management rather than fundoplication.…”
Section: Magnetic Sphincter Augmentationmentioning
confidence: 99%